Study of Mortality of Eucalyptus Plantations in the Mahi Ravines, Central Gujarat - Verma, Balvir; Singh, Bakshish; Patel, A P (Annals of Arid Zone, 2016)
Experimental plantations of Eucalyptus camaldulensis Dehn., (Bangalore) and Eucalyptus hybrid (Syn. Eucalyptus tereticornis Sm., Bangalore) were raised in 1963 on the sandy alluvium of ravine lands along the Mahi river at the farm of Soil Conservation Research, Demonstration and Training Centre, Vasad (Gujar&t). The plantations indicated stunted growth in 1965, and some trees started dying after growing to a height of 5-6 meters. Symptoms of chlorosis developed in the leaves of affected trees. Factors like rainfall, soil moisture, soil analysis and leaf analysis have been discussed in the context of the above performance of the plantations. The soil was also examined for the presence of any pathogens on the roots of the dying trees and in the associated root zone. The plantation has suffered due to soil moisture deficiency and lime induced chlorosis of the leaves.